Processing coping methods in expressive essays about stressful experiences: Predictors of health benefit. (June 2016) - Hoyt, Michael A; Austenfeld, Jennifer; Stanton, Annette L
This study distinguished constructive (e.g. planning/problem-solving) and unconstructive (e.g. worry) processing in expressive essays and their impact on depressive symptoms, healthcare visits, and physical symptoms. Affect labeling, achievement orientation, and insight utilization were examined as mediators. Essays from 43 medical students were coded; mediators were identified through linguistic text analysis. Outcomes were assessed at baseline and 3 months. Constructive processing predicted declining depressive symptoms (β = −.33, p < .05) and healthcare visits (β = −.61, p < .01). Unconstructive processing predicted increasing healthcare visits (β = .42, p < .05). Higher affect labeling mediated the effect of constructive processing, and lower achievement orientation mediated the effect of unconstructive processing.